Identifying different electronic transport mechanisms in nanoporous inorganic electrides – a combined study using Hall measurements and electron paramagnetic resonance spectroscopy. Issue 10 (24th February 2023) - Dinter, Julius K.; Lange, Jurek; Hofmann, Detlev M.; Plaza Fernández, J. Fabián; Post, Angel; Chatterjee, Sangam; Elm, Matthias T.; Klar, Peter J.
Abstract : Temperature-dependent Hall measurements and electron paramagnetic resonance spectroscopy reveal that three different transport mechanisms contribute to the electronic properties of the inorganic electride [Ca24 Al28 O64 ] 4+ (4e − ). Abstract : Mayenite [Ca24 Al28 O64 ] 4+ (2O 2− ) is a nanoporous compound, whose properties are strongly determined by its degree of reduction. It consists of a positively charged, subnanometer sized cage structure [Ca24 Al28 O64 ] 4+ and two additional oxygen ions O 2−, which ensure charge neutrality. The O 2− ions occupy 1/6th of the cages and can move almost freely between them. A transition from insulating behavior to metallic behavior occurs when replacing the O 2− ions in the cages by electrons, finally generating the electride [Ca24 Al28 O64 ] 4+ (4e − ). This wide tunability together with its mechanical and chemical stability make the [Ca24 Al28 O64 ] 4+ (2O 2− )(1− x ) (4e − ) x system highly attractive for various electronic device applications. However, a complete understanding of the charge transport mechanisms of the [Ca24 Al28 O64 ] 4+ (2O 2− )(1− x ) (4e − ) x system and their variation with the degree of reduction x is far from complete. Here, we present the characterization of a series of polycrystalline [Ca24 Al28 O64 ] 4+ (2O 2− )(1− x ) (4e − ) x with different x using Hall-measurements and electron paramagnetic resonance (EPR) spectroscopy in the full temperature range between 10 K and 300 K. The study of temperature dependence of the effective carrier concentrations, the effective mobility, and the spin relaxation processes provides detailed insight into the electronic properties of the material. Three different transport mechanisms are identified which dominate at different temperatures. The crossover-temperature between these mechanisms is observed in both types of experiments and depends on x, which determines the effective charge carrier concentration. In addition, the interplay of the three transport mechanisms explains discrepancies which occur when solely the EPR signal intensity is used as a measure of the effective carrier concentrations 4 x per unit cell volume of partially reduced [Ca24 Al28 O64 ] 4+ (2O 2− )(1− x ) (4e − ) x .